Biological Activities of Red and Green Algae from Visakhapatnam Coast - Satyalakshmi Siragam (Journal of Global Pharma Technology, 2018)
Objective: Determination of antibacterial, antioxidant, anti-inflammatory and anti-tumor activity of green and red algae collected from Visakhapatnam sea coast.Methods: In vitro methods are used for determination of biological activities of algal extracts. Diffusion method of microbiological assay was used for estimation of antibacterial activity. Reducing power and free radical scavenging method for determination of antioxidant activity of algae. In vitro anti-inflammatory activity was determined by egg albumin and erythrocyte stabilization. HeLa (Cervical carcinoma) cell lines are used for determination of anti-tumor activity.Results: Red algae Gracilaria corticata exhibited good antibacterial activity against selected test microorganisms. In vitro free radical scavenging method is used for determination of antioxidant activity of Caulerpa taxifolia and exhibited 48.76±0.08% of inhibition at 200 µg/mL. Gracilaria corticata exhibited good anti-inflammatory activity of 58% which was determined by in vitro method of erythrocyte stabilization and 66.75% by egg albumin method. Green algae Caulerpa taxifolia exhibited (IC50 = 32±1.2) remarkable antitumor activity on HeLa cell lines than control.Conclusion: Among two organic solvents used for extraction of active principles from marine algae, methanolic extracts showed better biological activity than the chloroform extract. Green algae Caulerpa taxifolia exhibited significant antioxidant and anti tumor activity than remaining two algal species. Red algae Gracilaria corticata showing remarkable anti-inflammatory activity in both the in vivo methods. This study expands the medicinal importance of marine algae collected from coastal regions like Visakhapatnam.